(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines the importance of learning a foreign language for modern enterprise employees in the context of globalization and the development of international business relations. The article highlights the economic benefits of such training, including expanding markets and increasing the competitiveness of companies. The benefits of training for improving communication and professional relationships in a multicultural environment, as well as its role in improving the skills and professional development of employees are also discussed. The article contains an analysis of the relevance of teaching foreign languages in modern business and provides examples of successful training programs implemented at enterprises. In conclusion, the importance of developing and supporting such programs for the effective functioning of enterprises in the international market is emphasized.